Hypoxia-Elicited Mesenchymal Stem Cell-Derived Small Extracellular Vesicles Alleviate Myocardial Infarction by Promoting Angiogenesis through the miR-214/Sufu Pathway - Lianbo Shao; Yihuan Chen; Jingjing Li; Jingfan Chao; Ziying Yang; Yinglong Ding; Han Shen; Yueqiu Chen; Zhenya Shen (Hindawi Limited, 2023)
Objective. Myocardial infarction is a leading cause of mortality worldwide. Angiogenesis in the infarct border zone is vital for heart function restoration after myocardial infarction. Hypoxia-induced MSC modification is a safe and effective approach for angiogenesis in clinical therapy; however, the mechanism still requires further investigation. In our study, we preconditioned human umbilical cord mesenchymal stem cells (huMSCs) with hypoxia and isolated the small extracellular vesicles (sEVs) to promote cardiac repair. We also investigated the potential mechanisms. Method. huMSCs were preconditioned with hypoxia (1% O2 and 5% CO2 at 37°C for 48 hours), and their sEVs were isolated using the Total Exosome Isolation reagent kit. To explore the role of miR-214 in MSC-derived sEVs, sEVs with low miR-214 expression were prepared by transfecting miR-214 inhibitor into huMSCs before hypoxia pretreatment. Scratch assays and tube formation assays were performed in sEVs cocultured with HUVECs to assess the proangiogenic capability of MSC-sEVs and MSChyp-sEVs. Rat myocardial infarction models were used to investigate the ability of miR-214-differentially expressed sEVs in cardiac repair. Echocardiography, Masson's staining, and immunohistochemical staining for CD31 were performed to assess cardiac function, the ratio of myocardial fibrosis, and the capillary density after sEV implantation. The potential mechanism by which MSChyp-sEVs enhance angiogenesis was explored in vitro by RT-qPCR and western blotting. Results. Tube formation and scratch assays demonstrated that the proangiogenic capability of huMSC-derived sEVs was enhanced by hypoxia pretreatment. Echocardiography and Masson's staining showed greater improvements in heart function and less ventricular remodeling after MSChyp-sEV transplantation. The angiogenic capability was reduced following miR-214 knockdown in MSChyp-sEVs. Furthermore, Sufu, a target of miR-214, was decreased, and hedgehog signaling was activated in HUVECs. Conclusion. We found that hypoxia induced miR-214 expression both in huMSCs and their sEVs. Transplantation of MSChyp-sEVs into a myocardial infarction model improved cardiac repair by increasing angiogenesis. Mechanistically, MSChyp-sEVs promote HUVEC tube formation and migration by transferring miR-214 into recipient cells, inhibiting Sufu expression, and activating the hedgehog pathway. Hypoxia-induced vesicle modification is a feasible way to restore heart function after myocardial infarction.